Fundamental Guideline for Writing an Academic Research Proposal and Some Common Mistakes - Samia Amin; Saiful A (Update Dental College, 2017)
A research proposal is an essential scheme of any research. The contentment of any research is relying on the outstanding quality of research proposal. Both the social and health science research proposal writing depends on numerous factors which may be quality benchmarks, budget, time frame and many more. A research proposal should provide an outline of research which helps a reader to understand the scope and value of research work. So, the aim of this article is to provide a brief fundamental ideas and guild lines for a new researcher as well as students. Update Dent. Coll. j: 2016; 6 (2): 01-05